Secure data access control with perception reasoning - Mateen, Abdul; Rauf, Abdul; Hanan Abdullah, Abdul; Ashraf, Mahmood (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2018)
In spite of all security issues in the cloud system, distributed cloud environment requires an access control model which should be context aware to handle all issues intelligently. It must include role activation process based on the user's context information. In role activation process, the knowledge of reason used for data collection and usage is declared; this can allow the administrator to declare the policies which are context based. Therefore, there is dynamic activation of role permission due to the association of role with context. The complications in the role based access control model reduced by classifying the users into classes or groups having their own access control standards. Access to specific resources and granting/ denying is based on requesting the user identity. Cloud environments consist of different entities, number of resources and user where general access control model fails to cover all the aspects. Here, in the proposed access control with perception reasoning, entities are extended using Extensible Access Control Mark-up Language (XACML) where trust module monitors the random and dynamic behavior of the user with recognizing and restricting the malicious user for illegal data access. By issuing and identity tag to malicious user includes classification of task and data tag with data in the database.